Pemberdayaan Masyarakat Desa Panjangrejo Bantul Yogyakarta sebagai Upaya Mewujudkan Desa Sehat Gigi dan Mulut 2030 - Pramudya Aditama; Leny Pratiwi Ariesandy; Fimma Naritasari; Nunuk Purwanti (Direktorat Pengabdian kepada Masyarakat Universitas Gadjah Mada, 2018)
Oral health problem in Indonesian has increased. Yogyakarta is the fourth province with the highest number oral health problem and the third province with the highest Effective Medical Demands (EMD) for oral health in Indonesia. This fact indicates that it needs the attention of many parties to solve this problem, especially in Yogyakarta. Through community empowerment, community will be able to independently maintain their oral health and can be expected to be one of a solution to overcome the existing problems.The establishment of Oral Health Cadre (KADEGI) is a form of community empowerment strategy in terms of human resource development. Community empowerment, using the Participatory Learning and Action (PLA) method, is very effective to help the KADEGI mastered several skills such as (a) able to do dental health education, (b) able to do early detection of oral disease and (c) able to refer oral health cases to the nearest public health services (puskesmas).The results of KADEGI's work in data collecting of oral health problem in Desa Panjangrejo showed that from 1.198 respondents who were examined, 64% of respondents had tooth cavities and 49% had debris and calculus. These data indicate that Desa Panjangrejo’s resident are still need special attention in oral health problem by various parties.